2020
DOI: 10.3389/fphar.2020.00892
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Invigorating Qi and Activating Blood Circulation Prescriptions in Treating Qi Deficiency and Blood Stasis Syndrome of Ischemic Stroke Patients: Study Protocol for a Randomized Controlled Trial

Abstract: Ischemic stroke (IS) is characterized by high morbidity and high mortality. The integration of Traditional Chinese medicine (TCM) and western medicine has shown promising benefits in relieving symptoms, promoting neurological recovery, and improving the quality of life of patients with IS. In TCM, Qi-deficiency along with blood-stasis (QDBS) syndrome is one of the common types of IS that is treated by invigorating Qi and activating blood circulation. In TCM theory, improving the corresponding degree of prescri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…As for the medication of cerebral I/R injury and BBB protection, amounts of literature indicated that various extracts or compound medicines from natural products show beneficial effects ( Li Y. et al, 2019 ; Yu et al, 2020 ). For instance, Buyang Huanwu decoction (BHD) and Tongxinluo (TXL), both consisting of herbal and animal medicines, are common TCM prescriptions used for treating Qi deficiency and blood stasis syndrome of ischemic stroke by efficacies of invigorating Qi and activating blood circulation ( Su et al, 2011 ; Wang Y. et al, 2020 ). Experimental studies revealed that BHD and TXL could alleviate cerebral I/R injury and exert protective effects on the BBB ( Liu et al, 2013 ; Chen et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…As for the medication of cerebral I/R injury and BBB protection, amounts of literature indicated that various extracts or compound medicines from natural products show beneficial effects ( Li Y. et al, 2019 ; Yu et al, 2020 ). For instance, Buyang Huanwu decoction (BHD) and Tongxinluo (TXL), both consisting of herbal and animal medicines, are common TCM prescriptions used for treating Qi deficiency and blood stasis syndrome of ischemic stroke by efficacies of invigorating Qi and activating blood circulation ( Su et al, 2011 ; Wang Y. et al, 2020 ). Experimental studies revealed that BHD and TXL could alleviate cerebral I/R injury and exert protective effects on the BBB ( Liu et al, 2013 ; Chen et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Under the guidance of the theory of "Inheriting the Essence, and Adherence and Innovation", due to a weak ability of BYHW in activating blood circulation and dredging collaterals, NXT, was proposed and manufactured by Buchang Pharmaceutical Co., Ltd.. NXT (national medicine permission number: Z20025001), obtained drug production approval in 1993, awarded National Chinese Medicine Protection Certificate in 2014, and was included in the National Basic Drug List (2012 edition) and the Chinese Pharmacopoeia (2015 edition). Over the past two decades, NXT has been used to treat more than 100 million patients, and can significantly improve the total effective rate of cardio/cerebro-vascular diseases [25].…”
Section: Discussionmentioning
confidence: 99%
“…Statisticians, independent of all the other processes, will conduct the statistical analyses by using SPSS version 15.0 for Windows (Chicago, IL, United States). The statisticians will calculate the mean, standard deviation, median, minimum, maximum, lower quartile (Q1), upper quartile (Q3) for quantitative data and describe numbers and percentages for qualitative data ( Wang et al, 2020 ). Comparisons between two groups will be conducted as following: t-tests or Wilcoxon rank-sum for normal or nonnormal ability distributions for quantitative data; chi-square test or Fisher’s exact test for qualitative data ( Wang et al, 2020 ).…”
Section: Methods and Designmentioning
confidence: 99%